2017
DOI: 10.1186/s12985-017-0681-0
|View full text |Cite
|
Sign up to set email alerts
|

The potential influence of human parainfluenza viruses detected during hospitalization among critically ill patients in Kuwait, 2013–2015

Abstract: BackgroundThe four types of human parainfluenza viruses (PIV) are important causes of community-acquired pneumonia, particularly in children; however, limited information exists about the incidence of PIV in critically ill patients. The aim of this study is to describe the spectrum, incidence and clinical features of PIV-associated infections diagnosed during the hospital stay of patients admitted to pediatric intensive care unit (PICU) and intensive care unit (ICU) of 5 medical centers across Kuwait.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Previous studies showed that the mortality of PMV infection among adults is 0-50%, depending on the virus type, immune status of the host, and severity of disease (28)(29)(30), which is consistent with our results. However, most of these studies focused on lower respiratory tract infections or acute respiratory infections affected by these PMVs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed that the mortality of PMV infection among adults is 0-50%, depending on the virus type, immune status of the host, and severity of disease (28)(29)(30), which is consistent with our results. However, most of these studies focused on lower respiratory tract infections or acute respiratory infections affected by these PMVs.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the outcomes of infectious diseases were influenced by hosts, pathogens, and environments ( 31 ). In some studies, clinical outcomes were only compared directly with disease severity of the three PMV infections and were not controlled for confounders ( 10 , 21 , 23 , 28 , 29 , 32 ). In our study, after adjustment for numerous potential confounders, we found that, compared with hMPV-P and hPIV-p, RSV-p was associated with increased risks for invasive ventilation, ICU admission, and 30-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Adults can also be infected; up to 11.5% of adult hospitalizations for RTIs attributed to HPIVs (31)(32)(33). An epidemiological study in Kuwait demonstrated that HPIVs were isolated from 2.6% of immunocompetent patients with viral infections requiring admission in pediatric and adult ICUs (34). Concerning HRhV, a recent epidemiological study in mechanically ventilated adult patients in five ICUs demonstrated that HRhV were the second most prevalent virus (5%) after HPIV (6%), independently of the cause of ICU admission (35).…”
Section: Introductionmentioning
confidence: 99%
“…et al [7] and was first associated with mild respiratory illness in young people. However, recent studies have indicated that it can cause more-severe infections, such as pneumonia and bronchiolitis, in children and elderly individuals [8][9][10][11][12], and in immunocompetent individuals as well as critically ill patients [13][14][15].…”
mentioning
confidence: 99%